Bioresponsive Microneedles with a Sheath Structure for H2O2 and pH Cascade‐Triggered Insulin Delivery. Issue 14 (26th February 2018) - Zhang, Yuqi; Wang, Jinqiang; Yu, Jicheng; Wen, Di; Kahkoska, Anna R.; Lu, Yue; Zhang, Xudong; Buse, John B.; Gu, Zhen
Abstract: Self‐regulating glucose‐responsive insulin delivery systems have great potential to improve clinical outcomes and quality of life among patients with diabetes. Herein, an H2 O2 ‐labile and positively charged amphiphilic diblock copolymer is synthesized, which is subsequently used to form nano‐sized complex micelles (NCs) with insulin and glucose oxidase of pH‐tunable negative charges. Both NCs are loaded into the crosslinked core of a microneedle array patch for transcutaneous delivery. The microneedle core is additionally coated with a thin sheath structure embedding H2 O2 ‐scavenging enzyme to mitigate the injury of H2 O2 toward normal tissues. The resulting microneedle patch can release insulin with rapid responsiveness under hyperglycemic conditions owing to an oxidative and acidic environment because of glucose oxidation, and can therefore effectively regulate blood glucose levels within a normal range on a chemically induced type 1 diabetic mouse model with enhanced biocompatibility. Abstract : New H2 O2 and pH cascade‐responsive nano‐sized insulin complex micelles (Ins‐NCs) are developed. Ins‐NCs are loaded into a microneedle (MN) patch consisting of an H2 O2 ‐scavenging sheath layer for enhancing biocompatibility. The insulin is specifically released in an oxidative and acidic microenvironment created by an enzymatic reaction with glucose oxidase under hyperglycemic conditions, therefore regulating blood glucose levels tightly.